Coordination as a function of skill level in the gymnastics longswing - Williams, G. K. R.; Irwin, G.; Kerwin, D. G.; Hamill, J.; Van Emmerik, R. E. A.; Newell, K. M. (Journal of Sports Sciences, 2016)
The purpose of this study was to investigate the nature of inter-joint coordination at different levels of skilled performance to: (1) distinguish learners who were successful versus unsuccessful in terms of their task performance; (2) investigate the pathways of change during the learning of a new coordination pattern and (3) examine how the learner`s coordination patterns relate to those of experts in the longswing gymnastics skill. Continuous relative phase of hip and shoulder joint motions was examined for longswings performed by two groups of novices, successful (n = 4) and unsuccessful (n = 4) over five practice sessions, and two expert gymnasts. Principal component analysis showed that during longswing positions where least continuous relative phase variability occurred for expert gymnasts, high variability distinguished the successful from the unsuccessful novice group. Continuous relative phase profiles of successful novices became more out-of-phase over practice and less similar to the closely in-phase coupling of the expert gymnasts. Collectively, the findings support the proposition that at the level in inter-joint coordination a technique emerges that facilitates successful performance but is not more like an expert`s movement coordination. This finding questions the appropriateness of inferring development towards a "gold champion" movement coordination.